Analisa Kenyamanan Kendaraan Multiguna Pedesaan Pada Kekasaran Jalan Iso 8608 - Nanda Pranandita (Manutech : Jurnal Teknologi Manufaktur, 2016)
The vehicle suspension system is an important part to minimize the vibration of the vehicle caused by road unevenness. The classification of the road surface in this study is based on the classification of road roughness "Good" according to ISO 8606. The analysis of passive suspension system in this research may explain the frequency response which is received by the motorists while driving. The full car model with 1 DOF riders used in this study, simulated by using the numerical simulation software. The frequency response analysis is done on the vertical movement of the driver. Based on the analysis performed, the highest acceleration of 2.375 m / s2 at a frequency of 3.258 Hz. This value indicates the condition of "Uncomfortable" based on the table of ISO 2631. This condition will cause the rider toexperience dizziness, therefore it is strongly advised motorists to avoid frequencies below 7 Hz.